The Economic Factors Affecting Family In Modern Vietnamese Society - THU, TRAN NGUYET MINH (The journal of contemporary issues in business and government, 2021)
Rapid modernization and economic development is accompanied with social changes in Vietnam, including changes in family relations in urban as well as rural areas. Among the changes, cohesion among family members becomes less tight and there is an increasing trend of divorce rate and among main reasons is economic reason and other individual and social causes. Using data from a sample survey conducted in 3 provinces/cities in Viet Nam in 2017, the author focuses on analysis of the factors that affect divorce decisions in modern Vietnamese society, thereby, contributing to mitigate the unwanted impacts of divorce, and to the implementation of Vietnam Family Development Strategy to 2020, vision to 2030.